Human Aspect of Financial Reporting Standards: A Review of Constraints in Implementing IFRS and Human Resource-Based Solutions - Ndabeni, Lindile; Mashigo, Polly (Journal of Global Economy, Business and Finance, 2025)
Purpose: This study aims to review the constraints in the way of complete absorption of International Financial Reporting System with the scope of human resource management related aspects. It also summarises the role of HRM in successful implementation of IFRS across various countries and industries. Design/ Methodology: This study analyses the role of people factor/human resource towards the successful adoption of IFRS for an organization. For this purpose the study is reviews 35 pre - published papers/ journals/ articles and summarises their key findings. Findings: The study finds that people factor is critically important for any organization to successfully implement IFRS conventions.